Evaluating the safety performance of China’s provincial construction industries from 2009 to 2017 - Kang, Liangguo; Wu, Chao (Journal of Civil Engineering and Management, 2020)
Performance evaluation in construction safety is of great importance to further improve upon safety management processes. This paper develops a data envelopment analysis (DEA) based framework to evaluate the construction safety performance at the macro level. The core of the method is to compare the output-input ratio of construction safety. Using the building practitioner, construction machinery and equipment, and construction area as the inputs, and value added of construction and death toll as the outputs, safety performance score is computed for the China’s provincial construction industries from 2009 to 2017. The results show that the number of benchmark provinces every year is between five and seven. The gap between the best-performing and underperforming province was relatively small in 2012 and big in 2014. Beijing, Qinghai, Hainan, Fujian, Chongqing, and Tianjin can be utilized as role models for the provinces that need to improve their performance in construction safety. The eastern region has the highest score in construction safety performance, followed by the western and central region. This study provides an effective solution to solve performance issue in regional construction safety and improves the tradition performance evaluation system to a certain extent.